Direct electrochemistry of glucose oxidase and sensing of glucose at a glassy carbon electrode modified with a reduced graphene oxide/fullerene-C60 composite1. Issue 95 (15th October 2015) - Thirumalraj, Balamurugan; Palanisamy, Selvakumar; Chen, Shen-Ming; Yang, Cheng-Yu; Periakaruppan, Prakash; Lou, Bih-Show
<x xml:space="preserve">Abstract</x> Schematic representation for the sensing of glucose at the RGO–C60/GOx composite.